Answer:
Step-by-step explanation:
Here,
f(x) = y
or , swapping x with y
now to solve for y we get
now we put f inverse x instead of y
I am done.
Answer:
6a^8/3a^4= (6/3)= 2
a^8/a^4= a^4
2a^4
(6/3)(a^8/a^4)= 2a^4
(6/3)(a^(8-4))= 2a^4
Step-by-step explanation:
The same line! hope this helps! i’m not 100% sure so if i’m wrong don’t flame me
Answer:
BElabora un esquema y resuelve el problema.
Step-by-step explanation:
Answer: constant of proportionality - the constant value of the ratio of two proportional quantities x and y; usually written y = kx, where k is the factor of proportionality.